2018
DOI: 10.1177/0310057x1804600508
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial Comparing Fibreoptic-Guided Tracheal Intubation through Two Supraglottic Devices: Ambu® Auragain™ Laryngeal Mask and LMA® Fastrach™

Abstract: The Ambu®AuraGain™ laryngeal mask (LM) (Ambu A/S, Ballerup, Denmark) is one of the few readily available second-generation supraglottic airway devices (SADs) that offer a conduit for fibreoptic-guided endotracheal intubation. We aimed to compare fibreoptic intubation through this device with the LMA® (laryngeal mask airway) Fastrach™ (Teleflex Medical, Co. Westmeath, Ireland), which has been a recommended dedicated rescue device for the management of the unanticipated difficult airway. This randomised controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
2
8
1
3
Order By: Relevance
“…The mean time taken in the insertion of ILMA was significantly higher than that observed in group 2. Similar observations were observed in a previous case study in which Ambu Aura Gain LM and LMA FastrachTM were compared [7]. A previous case study comparing Ambu Aura-i and LMA Supreme showed no significant difference in the time of insertion of both the device [8].…”
Section: Discussionsupporting
confidence: 81%
“…The mean time taken in the insertion of ILMA was significantly higher than that observed in group 2. Similar observations were observed in a previous case study in which Ambu Aura Gain LM and LMA FastrachTM were compared [7]. A previous case study comparing Ambu Aura-i and LMA Supreme showed no significant difference in the time of insertion of both the device [8].…”
Section: Discussionsupporting
confidence: 81%
“… Proporción del grado de facilidad de intubación orotraqueal. Usando la escala subjetiva de facilidad descrita por G. Preece y col. (6). Se trata de una escala de 0 a 10, en donde 0: extremadamente difícil y 10: extremadamente fácil.…”
Section: Medición De Resultadosunclassified
“…En la actualidad existen diferentes dispositivos supraglóticos disponibles para uso en pediatría; uno de ellos la máscara laríngea AuraGain, que por sus características de diseño permite la intubación orotraqueal guiada por fibrobroncoscopia (5), lo cual está respaldado por ensayos clínicos realizados en adultos (6)(7)(8), que reportan una porcentaje de intubación al primer intento del 91% al 100%, con un tiempo de intubación 21.4 a 127 segundos; además comparado con otros dispositivos supraglóticos tiene mejores porcentajes de visualización glótica y permite realizar una intubación traqueal más fácil y rápida. Sin embargo, en la población pediátrica este dispositivo no cuenta con estudios que evalúen su desempeño para ser usado como conductor en intubación con fibra óptica.…”
Section: Introductionunclassified
“…The ITLS-D2 is constructed for blind intubation but can also be combined with fibreoptic guided intubation through the ILTS-D. Undoubtedly, intubation endoscopy is the most reliable technique in this context, but it requires advanced skills and is, therefore, reserved for experienced airway management providers only [12]. However, the success rate using the ILTS-D2 was comparable with that of the FT-LM over all five attempts.…”
Section: Discussionmentioning
confidence: 99%